2019
DOI: 10.1098/rsta.2018.0217
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic magnetic hydrogels: design, structure and mechanical properties

Abstract: One contribution of 17 to a theme issue 'Heterogeneous materials: metastable and non-ergodic internal structures'.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 50 publications
1
28
0
Order By: Relevance
“…Alternatively, the use of a thick shell coating the nanoparticles was confirmed to hamper the gelation process, with the additional cost of requiring a larger concentration of hydrogelator to compensate for the bulkier nanocomposite [ 10 ]. On the other hand, forcing the supramolecular design strategies to conjugate the nanoparticles with the hydrogelator molecules has also been considered [ 25 , 26 , 27 ]. In general, these existing strategies for supramolecular magnetogels either imply complex fabrication steps and/or fail on the homogeneous incorporation of high concentrations of magnetic material and target drugs, which strongly limit their usability in theranostics.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, the use of a thick shell coating the nanoparticles was confirmed to hamper the gelation process, with the additional cost of requiring a larger concentration of hydrogelator to compensate for the bulkier nanocomposite [ 10 ]. On the other hand, forcing the supramolecular design strategies to conjugate the nanoparticles with the hydrogelator molecules has also been considered [ 25 , 26 , 27 ]. In general, these existing strategies for supramolecular magnetogels either imply complex fabrication steps and/or fail on the homogeneous incorporation of high concentrations of magnetic material and target drugs, which strongly limit their usability in theranostics.…”
Section: Introductionmentioning
confidence: 99%
“…The same group have also generated anisotropic magnetic hydrogels based on fibrin and alginate, with elastic moduli more than an order of magnitude greater than those of non-magnetic hydrogels. 77,78 Results have shown that the presence of functionalized MNP does not compromise the ex vivo and in vivo biocompatibility. 10,14,19 However, given the technical difficulty in obtaining these types of materials, especially through procedures that provide biocompatibility and scalability, the number of studies to date is very limited.…”
Section: Anisotropic Hydrogelsmentioning
confidence: 99%
“…Magnetic scaffolds are indeed reported to induce tissue damages repair through diverse approaches depending on the kind of tissue to be repaired. For instance, it is possible to design anisotropic magnetic scaffold able to mimic the specific tissue microenvironment for the repair of soft tissue containing hierarchically organized structures [ 126 ]. Most soft biological tissues consist of an extracellular matrix that can be considered a fibrous polymer network containing highly organized nanocomposite structures.…”
Section: Magnetic Scaffolds For Soft Tissue Regeneration Applicatimentioning
confidence: 99%